DIDACTIC PRINCIPLES IN TEACHING FINE ARTS - Khakimova, Gulnora Abdumalikovna; Azimova, Muxayyo Baratovna; Tuxsanova, Viloyat Radjabovna; Ibatova, Nigora Ismatovna (The journal of contemporary issues in business and government, 2021)
The article provides information on methods of teaching fine arts, new technological methods. The role of didactic principles in the teaching of fine arts is discussed. There are also opinions and conclusions about other methods.